Art in history, history in art studies in seventeenth-century Dutch culture - Freedberg, David (Issues & debates, 1991)
Art in History/History in Art: Studies in Seventeenth-Century Dutch Culture considers the potential for a reciprocally illuminating relationship between art history and history in light of recent methodological developments in both fields. The volume opens with contributions from a historian and an art historian; they examine the weaknesses of an art history without a social or economic history and lay the groundwork for the ensuing discussions of how the procedures and methods of each discipline may serve the aims of the other. A wide critique of approaches to the interpretation of realism in Dutch pictures forms the second section of the book. Included are critical views of recent iconographic developments, as well as contributions by a plant taxonomist and a marine historian. In the volume's third section new statistical and numerical models for the study of Dutch art in Dutch society are presented by three economic historians. The concluding essay provides a constructive critique of existing methodologies within each field. Art in History/History in Art: Studies in Seventeenth-Century Dutch Culture offers the most secure basis to date for future work on the interaction between the two disciplines and between the content of pictures and the cultures that produce them.